Kesehatan Mental Prespektif Ibn Miskawaih Tinjauan Atas Psikologi Islam - sasmita, riska; Nurfadil (Jurnal Spiritual Healing, 2024)
The purpose of this study was to study the importance of a sick and healthy mental condition and its healing methods, through the thoughts of Ibn Miskawaih by referring to one of his works, namely, Tahddzib Al-Akhlaq. This research found that Ibn Miskawaih's Islamic psychology was studied through the discourse of al-quwwah al-ghadabiyyah, which influenced the suffering of sadness or even depression, which had an impact on the human mind, using the discourse of philosophy of the soul, through philosophical studies, Ibn Miskawaih observes that the human soul's nervousness in processing and stimulating all aspects of reality has its roots in Suffering, depression, and sadness, mental illnesses often experienced by modern man.